The influence of situational strength on the relation of personality and situational judgment test performance - Jan-Philipp Freudenstein; Philipp Schäpers; Nomi Reznik; Talea Stolte; Stefan Krumm (International Journal of Selection and Assessment, 2023)
Situational strength theory has been used as a theoretical underpinning of person–situation processes that are linked to job performance. Accordingly, the link between personality traits and job performance increases in weak situations. Building on this research, similar mechanisms have been proposed for simulation-based selection tools, such as Situational Judgment Tests (SJTs), to explain how these measures work as predictors of job performance. However, underlying processes of SJT performance are subject to debate with some scholars arguing in favor of context-independent processes while others maintain that situations play an essential role. This study (N0.167em=0.167em707) examined whether the strength of situations in SJT items moderated the relation between personality and SJT performance. Results did not support the notion that personality is more strongly related to SJT performance when situations are weak. In fact, for some traits, the opposite may be true as more situational constraints led to an increase in the relation of extraversion, emotional stability, and SJT performance. The results add to an increasing body of research about psychological processes in SJTs. Limitations and implications for research and practice are discussed.
Keywords: 650; personality; selection; situational judgment tests; situational strength